2008
DOI: 10.1016/j.clinph.2008.09.020
|View full text |Cite
|
Sign up to set email alerts
|

EEG functional connectivity in term age extremely low birth weight infants

Abstract: Objective-The hypothesis is tested that electrocortical functional connectivity (quantified by coherence) of extremely low birth weight (ELBW) infants, measured at term post menstrual age, has regional differences from that of full term infants.Methods-128 lead EEG data were collected during sleep from 8 ELBW infants with normal head ultrasound exams and 8 typically developing full term infants. Regional spectral power and coherence were calculated.Results-No significant regional differences in EEG power were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 73 publications
(90 reference statements)
3
59
0
Order By: Relevance
“…Even though recent histological and MRI studies have enabled to highlight part of these mechanisms, the story is just beginning notably to understand how this development may be impacted by genetic, epigenetic, and environmental factors or early disturbances (e.g., in utero growth, preterm birth, hypoxic-ischemic lesion, neonatal stroke, and postnatal environment) (Ball et al, 2014;Fischi-Gomez et al, 2014;Gao et al, 2014;Grieve et al, 2008;Smyser et al, 2013). Despite challenges to studying fetuses and infants, combining complementary postmortem and in vivo approaches should provide a great opportunity to investigate the developing brain at different scales, from microstructure to functional organization.…”
Section: Resultsmentioning
confidence: 99%
“…Even though recent histological and MRI studies have enabled to highlight part of these mechanisms, the story is just beginning notably to understand how this development may be impacted by genetic, epigenetic, and environmental factors or early disturbances (e.g., in utero growth, preterm birth, hypoxic-ischemic lesion, neonatal stroke, and postnatal environment) (Ball et al, 2014;Fischi-Gomez et al, 2014;Gao et al, 2014;Grieve et al, 2008;Smyser et al, 2013). Despite challenges to studying fetuses and infants, combining complementary postmortem and in vivo approaches should provide a great opportunity to investigate the developing brain at different scales, from microstructure to functional organization.…”
Section: Resultsmentioning
confidence: 99%
“…Brain damage can still bring delayed cognitive, motor and sensory system dysfunction. Indeed, more than 50% of children and adolescents born preterm have needed the support of special education and monitoring by mental health services throughout their life 5,6,7 . While NICU is essential for the survival of newborns, the invasive environment, constant exposure to light, high noise level and noxious interventions generate stimuli that overload and damage the sensory system, and may have deleterious effects, changing the immature brain and its further development.…”
mentioning
confidence: 99%
“…The introduction of novel dense array EEG recording methods (30-130 electrodes) into neonatal work has opened the possibility to study spatial details in neonatal brain activity in both hospital and laboratory settings (Grieve et al, 2008;Odabaee et al, 2013;Omidvarnia et al, 2014;Tokariev et al, 2012;Wallois et al, 2009). The recent theoretical work has shown that the information content, or spatial richness, of EEG signal that can be recorded from the neonatal scalp is dramatically higher than what is conventionally thought (Grieve et al, 2003(Grieve et al, , 2004Odabaee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The conventional EEG analysis often relies on using variations of bipolar, linked mastoid reference or average reference montages, while the more recent, academically oriented studies (cf. Grieve et al, 2008;Omidvarnia et al, 2014;Roche-Labarbe et al, 2008;Tokariev et al, 2012) commonly rely on average and CSD montages. Our results show clearly that mixing signals results in a significant loss of specificity and sensitivity about spatial interactions, as in bipolar derivations, including common Cz reference.…”
Section: Effects Of Analysis Montagementioning
confidence: 99%
See 1 more Smart Citation